Equine road user safety: Public attitudes, understandings and beliefs from a qualitative study in the United Kingdom - Charles Musselwhite (Accident Analysis & Prevention, 2011)
Horse riders represent a significant group of vulnerable road user and are involved in a number of accidents and near misses on the road. Despite this horse riders have received little attention both in terms of academic research and transport policy. Based on literature on vulnerable road user safety, including attitudes to road user safety and behaviour of drivers and their relationship with cyclists and motorcyclists, this paper examines the attitudes and reported behaviour of drivers and horse riders. A total of 46 participants took part in six focus groups divided into four groups of drivers with little or no horse riding experience and two groups of frequent horse riders. Each group investigated five key topic areas stemming from the literature review on vulnerable road users including hazard perception, risk perception, emotion, attitudes to sharing the road and empathy. It was found that drivers and horse riders are not always aware of the same hazards in the road and that this may lead drivers to under-estimate the risk when encountering horses. Drivers often had good intentions to overtake horses safely, but were unaware of how vulnerable passing very wide and slow made them feel until they had begun the manoeuvre and hence quickly reduced such feelings either by speeding up or cutting in too soon. However, other than this, drivers had good skills when encountering horses. But these skills could be impeded by frustration when encountering a slow moving horse which was further compounded by a feeling, mainly by younger drivers, that horse riding was for leisure and as such should not get in the way of necessary work journeys. There is a need for drivers to be more aware of the potential hazards a horse rider faces on the road and these could be achieved through inducing empathy amongst drivers for horse riders, creating nudges for drivers in the environment and better education for drivers.--------------------------------------------------------------------------------